IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM MENGEMBANGKAN KOMPETENSI ABAD 21 SISWA SEKOLAH DASAR - Mutmainah, Siti Utami; Permata, Adinda Dyah; Kultsum, Ula Waliyah; Prihantin, Prihantin (Universitas Tanjungpura, 2022)
This study aims to determine the form of implementation of the scientific approach to developing 21st-century competence of elementary school students. The technique used in this research is qualitative with the literature study method. The data obtained are sourced from scientific books, research reports, scientific essays, theses and dissertations, regulations, and written sources, both printed and electronic, that are relevant to the research objectives. The results showed that the scientific approach developed critical thinking and problem-solving skills, creativity and innovation, communication, and collaboration in elementary school students. The development of essential thinking competence is applied in argument analysis and evaluation activities. The result of creative thinking competence tends to be encouraged by the school environment, for example, through work independence, stimulation, and utilization of surrounding objects. Communication competence can be developed through role-playing activities and productive language activities. Then, the development of collaboration competencies can be carried out by working on group project activities. Thus, the scientific approach is considered ideal to be applied in learning activities to develop 21st-century skills of elementary school students.